A Comment on "The Relative Efficiency of Skilled Labor across Countries: Measurement and Interpretation" by Rossi (2022) - Santiago Campos-Rodríguez; John Chung (Institute for Replication (I4R), 2023)
Rossi (2022) examines the relative efficiency of skilled workers across countries. He finds the elasticity of skill efficiency with respect to GDP per worker is 1.4 and that the relative human capital accounts for only about 9 percent. We reproduce the paper's main findings and test the sensitivity of the results to (1) alternative samples and (2) additional controls for determining wages. We find the results remain robust to these alternative specifications, and the estimated values of the key elasticities remain nearly unchanged.
Keywords: 330